Perbedaan Keberhasilan Pemberian ASI Eksklusif pada Ibu Bekerja dan Tidak Bekerja di RSU Hermina Kota Bogor - Aqila Tsusayya Putri; Stella T Hasianna; July Ivone (Journal of Medicine and Health, 2020)
Breast milk has important and beneficial nutrients for the growth and development of an infant, resulting in the recommendation of exclusive breastfeeding until the child is 6 months old. This study aimed to determine the difference in the success of exclusive breast milk provision between working and non-working mothers. This is an observational analytic study with a cross-sectional design, with working and non-working mothers as the independent variable and exclusive breast milk provision as the dependent variable. This study involved 52 mothers that met inclusion criteria and data were taken through a questionnaire at Hermina Bogor Public Hospital. Data were then analyzed with the Chi-Square statistical test. The results showed that 15 (57.70%) working mothers provided breastmilk exclusively and 19 (73.10%) non-working mothers also provided breastmilk exclusively for their babies. The statistical analysis showed a p-value of 0.191 (> 0.05), showing no significant relationship between the working status of the mother with the success of exclusive breast milk provision. It was concluded there was no significant difference in the success of exclusive breast milk provision between working and non-working mothers. Keywords: Exclusive breast milk provision; working mothers; non-working mothers